Ubuntu Linux bible : featuring Ubuntu 10.04 LTS - Von Hagen, William (Wiley, 2010)
"Ubuntu is a free, open-source, Linux-based operating system that can run on desktops, laptops, netbooks, and servers. If you've joined the millions of users around the world who prefer open-source OS-and Ubuntu in particular-this book is perfect for you. It walks you through the very latest on Ubuntu 9.10 and 10.04, also discussing applications from the KDE version Kubuntu, with pages of step-by-step instruction, helpful tips, and expert techniques"--Resource description page